Analysis Risk Factors For Acute Otitis Media Patients at ENT Clinic Malang Muhammadiyah University General Hospital - Indra Setiawan; Churochman, Miftha; Winarno, Sahda Ahnaf; Mariyam Abdullah (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Acute Otitis Media (AOM) is a common disease worldwide, including in low-income and developing countries such as Indonesia. The incidence of AOM varies among countries. Indonesia is ranked fourth in Southeast Asia with the highest prevalence of ear disease at 4.6%. To determine the risk factors for AOM and the relationship between each risk factor in patients at the Ear Nose Throat (ENT) clinic of Malang Muhammadiyah University General Hospital (MMUGH). This study used a descriptive analytic method with a cross sectional study approach. The study was conducted from March to June 2024. Risk factors for AOM in includes gender, age, history of allergies, Acute Respiratory Infection (ARI), cigarette exposure, pollution exposure, and family history. Pollution exposure was the most dominant risk factor for AOM.